Pengaruh Terapi Musik Klasik terhadap Intensitas Nyeri pada Inpartu Fase Aktif Kala I Persalinan di Praktek Mandiri Bidan Pertiwi Sengkang Kabupaten Wajo - Warlinda Warlinda; Yusda Seman MY; Enggar Enggar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to determine the effect of classical music therapy on pain intensity in active phase in-partu mothers during the first stage of labor at the Independent Midwife Practice of Pertiwi Sengkang, Wajo Regency. This type of research is quantitative research using the Pre-experimental design method